Case Report: Congenital Perineal Lipoma Associated With Additional External Genitalia Anomalies - Tocchioni, Francesca; Caporalini, Chiara; Buccoliero, Annamaria; Facchini, Flavio; Ghionzoli, Marco; Morini, Francesco (Frontiers in Pediatrics, 2022)
Perineal lipoma is an uncommon congenital benign tumor sometimes associated with genitourinary or anorectal malformations. Accessory scrotum and accessory labioscrotal fold are infrequent features, often concurrent with perineal tumors. We describe a single institution experience with three consecutive cases of perineal lipoma associated with external genital anomalies and a literature review.